APPLICATION LIDAR AND POINT CLOUDS FOR 3D MODELING OF MUSEUM OBJECT - Ika Asti Astuti; Ahmad Subekti (Jurnal Riset Informatika, 2022)
A museum is an institution intended for the general public that collects, cares for, presents, and preserves the community's cultural heritage for study, research, and pleasure or entertainment. The museum is undoubtedly one of the educational places for the community because it has many historical objects. It provides an opportunity to make the museum a vital place to be developed in a virtual form, such as Augmented Reality or Virtual Reality. However, one problem in developing virtual media is the 3D modeling of objects for interior design in museums. LiDAR (Light Detection And Ranging) is a near real-time 3D positioning technology. A point cloud collects data points in a 3D coordinate system, generally defined by x, y, and z coordinates. Both of these technologies can be used to create 3D object models quickly. The final result of this research is applying LiDAR & point cloud as a 3D modeling technique and assessing the accuracy of using these techniques for 3D modeling of the museum object